Fun for the secret seven - Blyton, Enid (Knight Books London, 1992)
Enid Blyton is one of the best-known writers of children's fiction, with over 750,000 of her books sold each year worldwide. This is one of a series of adventures with the Secret Seven which have been carefully and sympathetically updated for today's young readers.